Blueberries for the Queen - Paterson, John (HarperCollins, 2004)
In the summer of 1942, when Queen Wilhelmina of the Netherlands lives down the road from his family's house in Massachusetts, young William decides to take her some of the blueberries he has picked. Includes historical notes.